Developing Local Culture-Based Teaching Module to Enhance Children’s Cultural Appreciation - Nani Nuriani; Dadi Setiadi; Asrin Asrin; Sri Subarinah; Sukri Sukri (Academia Open, 2025)
General background: Early childhood education plays a pivotal role in shaping cognitive, affective, and psychomotor development, with cultural integration enhancing meaning and identity. Specific background: In North Lombok, despite rich traditions, globalization has eroded cultural practices and language use among children, creating an urgent need for culturally grounded pedagogy. Knowledge gap: Previous studies emphasized cognitive aspects of local culture but lacked comprehensive teaching modules explicitly designed to foster cultural appreciation in early childhood. Aims: This study aimed to develop and validate a local culture-based teaching module for early childhood education in North Lombok. Results: Using a modified 3-D model (define, design, develop), the module was validated by experts (design 79%, language 87%, material 96%, practitioner 94%) and trialed with 92 students, achieving an average effectiveness score of 88%, categorized as “developing as expected.” Novelty: Unlike prior works, this module integrates multiple cultural elements (games, food, clothing, customs, language) into both print and digital formats, with comprehensive components (CP, TP, ATP, IKTP, RPPH, assessments, and LKS). Implications: The findings demonstrate that a culturally based module can effectively enhance children’s appreciation of local heritage, offering both practical tools for educators and theoretical contributions to culture-based early education Highlights: Integration of local culture strengthens children’s identity. Validated module shows high feasibility and effectiveness. Novel contribution: complete print–digital learning tools. Keywords: Teaching Module, Local Culture, Early Childhood, Cultural Appreciation